THE POWER OF POSITIVITY: THE ROLES OF PROSOCIAL BEHAVIOR AND SOCIAL SUPPORT TOWARD GRATITUDE - Yunanto, Taufik Akbar Rizqi (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
Abstract ? Existing literature demonstrates that gratefulness is a critical determinant for individuals? well-being and their quality of interpersonal relationships. A sense of gratefulness provides a perspective in which individuals could have a positive evaluation in life, including the way they view challenges. Positive appreciation of life?s challenges would allow individuals to increase their coping ability and would motivate them to do prosocial behavior. This study aims to determine the role of prosocial behavior and social support to individuals? sense of gratefulness. Participants in this study consisted of 250 participants aged between 13?55 years old. The instruments used in this research were Gratitude Questionnaire, Philosophies of Human Nature Altruism Scale, and Social Support Scale. Multiple regression analysis was used to analyze the data. The result revealed a strong contribution between prosocial behavior and social support toward gratitude. Gratitude and prosocial behavior contribute in enabling individuals to have a positive evaluation of life. Abstrak ? Studi terdahulu menunjukkan bahwa rasa bersyukur menjadi penentu yang penting bagi kesejahteraan individu dan kualitas hubungan interpersonal mereka. Bersyukur memberikan perspektif yang dapat membuat individu memiliki evaluasi positif mengenai hidupnya, termasuk dalam memaknai tantangan. Individu yang memandang penderitaan sebagai sesuatu yang positif dapat meningkatkan kemampuan mengatasi masalah yang baru dan termotivasi melakukan perilaku prososial. Penelitian ini bertujuan untuk mengetahui peran perilaku prososial dan dukungan sosial terhadap tingkat kebersyukuran seseorang. Partisipan dalam penelitian ini terdiri dari 250 partisipan dengan rentang usia 13-55 tahun. Instrumen yang digunakan dalam penelitian ini adalah Gratitude Questionnaire, Philosophy of Human Nature Altruism Scale, dan Social Support Scale. Analisis data dalam penelitian ini menggunakan analisis regresi berganda. Hasil analisis menunjukkan bahwa terdapat sumbangan yang positif perilaku prososial dan dukungan sosial terhadap tingkat kebersyukuran. Rasa syukur dan perilaku prososial dapat membuat seseorang memiliki evaluasi yang positif dalam kehidupannya.